Cold War Space Sleuths The Untold Secrets of the Soviet Space Program - Phelan, Dominic; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Cold War Space Sleuths reads like a Cold War espionage novel, but the reality of the story about the dedicated amateur observers bent on finding out about Soviet spaceflight during the Cold War is just as exciting and absorbing. Told in the sleuth's own words, each chapter unfolds a piece of the hidden history of what was happening behind the Iron Curtain. Coming from all over the world, including Russia itself, the amateur spies give first-hand accounts of often-forgotten aspects of the Cold War space race. Amongst others, their stories include: - the history of the Kettering Group; - looking inside the Russian archives; - unsolved mysteries, such as why cosmonauts were airbrushed out of the official archives; - reading between the lines of the Soviet media; - the impact of Gorbachev's glasnost on sleuthing; - new research, including chapters by James Oberg, Asif Siddiqi, and Bart Hendrickx.
Foreword -- Editor's introduction -- Acknowledgements -- Chapter 1: Space sleuths and their 'scoops' Dominic Phelan -- Chapter 2: Hidden in plain view Brian Harvey -- Chapter 3: The satellite trackers Sven Grahn -- Chapter 4: Cosmonauts who weren't there James Oberg -- Chapter 5: The view from Paris Claude Wachtel and Christian Lardier -- Chapter 6: Orbital elements of surprise Phillip Clark -- Chapter 7: Adventures in Star City Bert Vis -- Chapter 8: Russian-language sleuthing Bart Hendrickx -- Chapter 9: People and archives Asif Siddiqi -- Chapter 10: Urban cosmonauts and space historians David J. Shayler -- Contributors -- Index.
Keywords: Engineering; Astronomy; Astronautics; Engineering; Aerospace Technology and Astronautics; Popular Science in Astronomy; Security Science and Technology